Pelestarian Cerita Rakyat Lokal melalui Program Buku Bergulir dan Pelatihan Storytelling - Afrizal, Mohamad; Reykasari, Yunita; Anggraeni, Astri Widyaruli (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2026)
The low reading interest in local folklore among the younger generation and the dominance of global culture pose a serious challenge to the preservation of cultural heritage in Indonesia. To address this, a community service program was carried out in Sumbersari Village, Jember, involving 24 PKK mothers. The program focused on two main strategies: a Rolling Book Program to improve folklore literacy and a Storytelling Workshop to equip participants with effective storytelling skills. Using the Participatory Action Research (PAR) method, the program successfully identified problems such as a lack of understanding of moral values in folklore and a minimal habit of telling stories within families. The evaluation results showed significant success, with 90.8% of participants expressing high satisfaction and agreement. The program successfully fostered the participants' awareness and commitment to continue the storytelling tradition and the Rolling Book Program independently. The sustainability of the program will be pursued through monthly rotation of folklore books and community book donations, although challenges such as limited books and the need for more varied interactive activities still exist. Overall, this program proves that folklore preservation can be done effectively through a participatory and educational approach, which not only improves literacy and skills but also strengthens the cultural foundation at the community level. === Minimnya minat baca cerita rakyat lokal di kalangan generasi muda dan dominasi budaya global menjadi tantangan serius bagi pelestarian warisan budaya di Indonesia. Untuk mengatasinya, sebuah program pengabdian masyarakat dilaksanakan di Kelurahan Sumbersari, Jember, yang melibatkan 24 ibu-ibu PKK. Program ini berfokus pada dua strategi utama: Program Buku Bergulir untuk meningkatkan literasi cerita rakyat dan Pelatihan Storytelling untuk membekali peserta dengan keterampilan mendongeng yang efektif. Menggunakan metode Participatory Action Research (PAR), program ini berhasil mengidentifikasi masalah, seperti kurangnya pemahaman nilai moral dalam cerita rakyat dan minimnya kebiasaan mendongeng dalam keluarga. Hasil evaluasi menunjukkan keberhasilan signifikan, di mana 90,8% peserta menyatakan sangat puas dan setuju. Program ini berhasil menumbuhkan kesadaran dan komitmen peserta untuk melanjutkan tradisi mendongeng serta Program Buku Bergulir secara mandiri. Keberlanjutan program akan diupayakan melalui rotasi buku cerita rakyat bulanan dan penggalangan donasi buku dari komunitas, meskipun tantangan seperti keterbatasan buku dan perlunya variasi kegiatan interaktif masih ada. Secara keseluruhan, program ini membuktikan bahwa pelestarian cerita rakyat dapat dilakukan secara efektif melalui pendekatan partisipatif dan edukatif, yang tidak hanya meningkatkan literasi dan keterampilan, tetapi juga memperkuat fondasi budaya di tingkat komunitas.